JADIDISM IS ETERNAL SCIENCE IN THE MEMORY OF GENERATIONS (Multidisciplinary Journal of Science and Technology, 2024)
The Jadid movement is a manifestation of enlightenment in philosophy and science. We felt it was important to discuss the sociophilosophical aspects of the Enlightenment and the Enlightenment movement, or Jadidism, in this article.